International Federation of Head Neck Oncology Society 5th World Congress/American Head Neck Society 2014 update - Sharma, Shilpi; Chaukar, Devendra A. (Indian Journal of Medical and Paediatric Oncology, 2014)
Head neck cancer is an important health problem with high morbidity and mortality. Early detection and adequate treatment improve prognosis significantly. Thus creating awareness among clinicians is an important step toward control of head neck cancer and reducing its overall burden. We here provide an update on the International Federation of Head Neck Oncology Society/American Head Neck Society 2014 held between July 26, 2014 and July 30, 2014 in New York.
Keywords: Head Neck Cancer; IFHNOS; AHNS